Keefektifan Strategi 3M (Meniru, Mengolah, dan Mengembangkan) dalam Pembelajaran Menulis Teks Eksplanasi pada Siswa - Riswan Riswan; Salam Salam; Muhammad Saleh (Indonesian Journal of Pedagogical and Social Sciences, 2021)
Abstract. This study aims to (1) describe the results of learning to write explanatory texts using expository strategies in the control class; (2) describe the results of learning to write explanatory texts using the 3M strategy in the experimental class; and (3) testing the effectiveness of the 3M strategy in writing explanatory texts. This type of research is experimental research. The research design used was pretest-posttest control grub design. The data in this study are student learning outcomes data. The research instrument consisted of research guidelines for writing explanatory texts. Data collection techniques were carried out through observation, pretest, treatment and posttest. Data analysis techniques used in analyzing the data are descriptive analysis and inferential analysis.  The results of the study reveal student learning outcomes in the control class using expository strategies, student learning outcomes in the experimental class using the 3M strategy, and the effectiveness of the 3M strategy in learning to write explanatory texts. (1) In the control class, the results obtained by students on the pretest (pretest) were categorized as less effective. Only one student scored in the effective category and five students scored in the moderately effective category out of a total of 26 students, the average score on this test was 62.15. Meanwhile, the results of the final test (posttest) are still categorized as less effective. Only one student scored in the effective category and six students in the moderately effective category out of a total of 26 students, with an average score of 65.59. (2) In the Experiment class, the results obtained by students in the initial test (pretest) were categorized as less effective. Only one student scored in the effective category and five students scored in the moderately effective category out of a total of 26 students, the average score on this test is 63.03. Meanwhile, the results of the final test (posttest) after the 3M strategy was implemented were categorized as quite effective. Of the 26 students who took part, as many as 24 students were categorized as quite effective, while 2 students were categorized as less effective. Keywords: Explanatory Texts, 3M Strategy, Writing Skill